Testing of a standardised protocol for visual health assessment of southern right whales (Eubalaena australis) - Moles, Matej (Department of Biological Sciences, 2024)
Since the late 1960s, southern right whales (Eubalaena australis) have been studied extensively in their coastal calving grounds (including South Africa). These studies have indicated a strong recovery of the species post-whaling. However, in most recent years, a decrease was observed in reproductive rates and coastal prevalence of the South African population, raising concerns about continued population recovery. As reproductive success and the migratory behaviour of this capital breeder is strongly mediated through body condition and overall health, understanding the past and current state of these parameters is crucial in understanding the observed population-level changes. The aim of this project was to build on the global, standardised qualitative visual health assessment protocol (Charlton et al., 2021), and assess the different parameters in relation to quantitative data on body condition. A dataset of 78 non-unique whales photographed in September of 2019 and 2021 was used for the analysis. Results showed that there is a moderate relationship between qualitative and quantitative body condition measurements, but only on 2 levels. This suggests that body condition of southern right whales can be scored visually relatively accurately to be either good or poor, allowing retrospective analyses of historical aerial images. Results of the study further showed that the other visual health parameters, known to be indicators of health in the species, did not correlate with quantitative, nor qualitative measurements of body condition. This suggests that, at least in South African southern right whales, poor body condition does not necessarily reflect poor health, and that thus all health parameters need to be evaluated in order to assess health condition of individual whales. This study advances our knowledge and understanding of how to assess visual health in southern right whales and concludes that body condition alone may not be enough to detect individuals in poor health.